Analisis Faktor-Faktor yang Mempengaruhi Prediksi Kenaikan Tekanan Darah Pasien Hipertensi di Rsud Dr. Pirngadi Medan - Hafizurrahman Hafizurrahman; Muharni Saputri; Desy Nathalia Siahaan; Feny Hasanah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Hypertension is a significant global health issue that can lead to serious complications if not properly managed. This study aims to analyze the factors influencing the prediction of blood pressure increase in hypertension patients at RSUD Dr. Pirngadi Medan. The research employs a quantitative approach with a descriptive-analytical design. Data were collected through patient medical records and questionnaires covering variables such as age, gender, nutritional status, stress levels, dietary patterns, and family medical history. Data analysis was conducted using logistic regression techniques to identify significant factors affecting blood pressure changes. The results indicate that age, nutritional status, and stress levels are significant factors influencing the prediction of blood pressure increase in hypertension patients. This study is expected to provide additional insights for more effective hypertension prevention and management strategies at the hospital and contribute to the development of better health policies.